Identification of successful competitive combinations in the section of kickboxing pointfighting - A.A. Poteryakhin; V.L. Kondakov; А.N. Usatov; V.I. Bocharova (Theory and Practice of Physical Culture, 2023)
Objective of the study was to identify effective competitive combinations in the point fighting kickboxing section, based on an assessment of the results of the performances of winners and prize-winners at major international competitions. Methods and structure of the study. In the course of the study, a theoretical analysis and generalization of scientific data, a video analysis of the competitive fights of the semi-finals and finals of the Cups and Championships of Russia, Europe and the world in the point fighting section in different age categories were carried out. Results and conclusions. We conducted a video analysis of the semi-finals and finals of the Cups and Championships of Russia, Europe and the world in the point fighting section in different age categories from 7 to 18 years old. It should be noted that athletes from the age of 7 years old are allowed to all European and world tournaments, and in Russia only from 10 years old, where they hone their basic technique in the point fighting section. In the course of the study, we have identified and presented effective competitive combinations in the point fighting kickboxing section for athletes of different age categories and gender. The use of effective competitive combinations in the kickboxing point fighting section helps athletes earn the maximum number of points per round and, accordingly, win the most prestigious tournaments in Russia, Europe and the world. In this study, effective competitive combinations were identified in the kickboxing point fighting section for athletes in different age categories performing at the Championships and Cups of Russia, Europe and the world.